Parâmetros metabólicos e histológicos de jundiás (Rhamdia quelen) expostos à formulação comercial do herbicida 2,4-diclorofenoxiacético (2,4-d) - Cattaneo, Roberta (2009)
2,4-Diamin (2,4-D), or 2,4 dichlorophenoxyacetic acid is a systemic herbicide widely used in the world to control of broadleaf weeds. Agrochemicals of various classes are considered essential to agricultural development, but owing to toxic effects some of them can affect ecosystems through environmental contamination of soil and water. The presence of herbicides in aquatic system can contaminate fish and consequently, others animals, which feed on fish, causing indirectly contamination. Thus, the objective of this study was to investigate the effects of commercial formulation of herbicide 2,4-D concentrations of 400, 600 and 700 mg L−1, on metabolic parameters, acetylcholinesterase (AChE) activity and liver histological evaluation of silver catfish (Rhamdia quelen) exposed for 96 h. AChE activity increased in brain (600 and 700 mg L−1) and decreased in all concentrations tested in muscle tissue. Hepatic glycogen was reduced after 2,4-D exposure ranging from 47.7% (400 mg L−1) and 59.3% (700 mg L−1). Hepatic tissue showed lactate reduction at all 2,4-D concentrations tested and glucose was reduced only at 700 mg L−1. In the highest concentration tested hepatic glycogen, glucose reduced and plasma glucose levels increased. White muscle tissue showed glycogen reduction in fingerlings exposed to all herbicide concentrations and glucose reduction at 700 mg L−1. Muscle lactate levels increase at all 2,4-D concentrations tested. Vacuolation of hepatocytes and changes in their arrangement cords were observed by histologic al analysis in the group treated with 700 mg L−1 2,4-D. These results suggest that silver catfish exposed to 2,4-D concentrations near CL50 showed metabolic and histological responses to compensate some stress caused by herbicide exposure. Taken together parameters measured can be used as biomarkers to monitor fish contaminating by 2,4-D.